Microbiological outcomes from different periodontal maintenance interventions: a systematic review - Patricia Daniela Melchiors ANGST; Amanda Finger STADLER; Rui Vicente OPPERMANN; Sabrina Carvalho GOMES (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract This study aimed to investigate the differences in the subgingival microbiological outcomes between periodontal patients submitted to a supragingival control (SPG) regimen as compared to subgingival scaling and root planing performed combined with supragingival debridement (SPG + SBG) intervention during the periodontal maintenance period (PMP). A systematic literature search using electronic databases (MEDLINE and EMBASE) was conducted looking for articles published up to August 2016 and independent of language. Two independent reviewers performed the study selection, quality assessment and data collection. Only human randomized or non-randomized clinical trials with at least 6-months-follow-up after periodontal treatment and presenting subgingival microbiological outcomes related to SPG and/or SPG+SBG therapies were included. Search strategy found 2,250 titles. Among these, 148 (after title analysis) and 39 (after abstract analysis) papers were considered to be relevant. Finally, 19 studies were selected after full-text analysis. No article had a direct comparison between the therapies. Five SPG and 14 SPG+SBG studies presented experimental groups with these respective regimens and were descriptively analyzed while most of the results were only presented graphically. The results showed that both SPG and SPG+SBG protocols of PMP determined stability in the microbiological results along time. Nevertheless, new studies comparing these interventions in PMP are needed, especially if the limitations herein discussed could be better controlled.